Mistletoe fig (Ficus deltoidea Jack) leaf extract prevented postmenopausal osteoarthritis by attenuating inflammation and cartilage degradation in rat model - Che Ahmad Tantowi, Nur Adeelah; Hussin, Paisal; Lau, Seng Fong; Mohamed, Suhaila (Lippincott Williams & Wilkins, 2017)
Objective: Ficus deltoidea Jack (mistletoe fig) is an ornamental plant found in various parts of the world and used as traditional herbal medicine in some countries. This study investigated the potential use of F deltoidea leaf extract to mitigate osteoarthritis (OA) in ovariectomized (estrogen-deficient postmenopausal model) rats and the mechanisms involved. Diclofenac was used for comparison.